Seismic performance validation for RC building structures damaged by Durres earthquake, Mw6.4, 26 November 2019, Albania - Vitanova, M.; Bogdanovic, A.; Bozinovski, Z.; Edip, K.; Bojadjieva, J.; Delova, E.; Zafirov, T. (Springer Science and Business Media LLC, 2022)
The earthquake that took place at 03:56 local time on November 26, 2019, with Mw = 6.4, struck the west part of Albania and caused heavy damages to many public and residential buildings in the districts of Durres, Tirana, Lezha, Shkodra, Diver, Berat and the surrounding areas. Immediately after the earthquake, teams from the Institute of Earthquake Engineering and Engineering Seismology arrived and made rapid visual assessment of 169 damaged buildings in the affected area. During the inspection, severe damages to structural and nonstructural elements were found. This paper shows the analytical proof of the seismic behaviour of the structures in which damages were observed during visual assessment. Elastic (static and equivalent seismic force) analyses of elements were performed up to ultimate state of strength along with dynamic analyses of low-, mid- and high-rise buildings with different structural systems and characteristics corresponding to the period of their construction and the design legislation for such type of structures in Albania. The ductility and displacement capacities were defined for each of these groups of structures, while dynamic analysis was performed to define the displacements and the ductility caused by the real earthquake record and the intensity of the earthquake recorded in Durres. The results from the analyses confirm the behaviour of low- and mid-rise structures under this earthquake considering that damages observed on-site completely correspond to damages that occur under the displacements obtained from the analytical investigations. Since highrise buildings were not found in the stricken region, their behaviour under an earthquake with the same characteristics as the one that took place in November 2019 was predicted applying the same methodology used for the low- and mid- rise buildings.
Keywords: Durres earthquake; Seismic performance; Displacement capacity